1996
DOI: 10.1093/toxsci/29.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Acetaminophen Hepatotoxicity by a Single Dose of Clofibrate: Effects on Selective Protein Arylation and Glutathione Depletion

Abstract: Previous reports demonstrated that repeated administration of peroxisome proliferators protects against acetaminophen (APAP) hepatotoxicity in mice. This protection was associated with a decrease in APAP's selective protein arylation and glutathione depletion. This study was conducted to determine if a single dose of clofibrate (CFB), rather than repeated doses, would similarly prevent APAP toxicity. CD-I male mice received a single dose of 500 mg CFB/kg and controls were given corn oil 24 hr prior to APAP cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…First, covalent binding of 14 C‐APAP was not different between DB and non‐DB mice. Second, selective protein arylation of cytosolic acetaminophen binding proteins, which has served as an indirect indicator of net availability of reactive electrophile in the liver, was also similar between non‐DB and DB mice (11, 38). Third, the degree of GSH depletion was also similar between non‐DB and DB mice, further strengthening the observation that equal bioactivation occurred in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…First, covalent binding of 14 C‐APAP was not different between DB and non‐DB mice. Second, selective protein arylation of cytosolic acetaminophen binding proteins, which has served as an indirect indicator of net availability of reactive electrophile in the liver, was also similar between non‐DB and DB mice (11, 38). Third, the degree of GSH depletion was also similar between non‐DB and DB mice, further strengthening the observation that equal bioactivation occurred in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Livers were homogenized (10% w/v) in a buffer containing 0.25 M sucrose, 10 mM Tris-HCl, 1 mM MgCl 2 , pH 7.4 (STM buffer). Homogenates were centrifuged at 9000 ϫ g. The resultant supernatant was centrifuged at 105,000 ϫ g for 1 h (Manautou et al, 1994(Manautou et al, , 1996. Cytosolic fractions were collected and stored at -80 0 C until needed.…”
Section: Assessment Of Selective Protein Arylation Due To Apapmentioning
confidence: 99%
“…Interestingly it has been reported that flavonoids and saponins which are present in Ph.Cr also activates PPAR-α system contributing in prevention of CCL 4 and paracetamol-induced hepatotoxicity [19,20]. This mechanism of activating PPAR-α system could be attributed to role of flavonoids and saponins present in Parthenium hysterophorus, playing role in prevention of CCL 4 and paracetamol-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%